OPTIMIZING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT THROUGH E-LEARNING METHOD WITH WHATSAPP APPLICATION AT STUDENTS OF SMA NEGERI 1 BUKO - Yustira Kharlina Tangiduk; Nurmin Samola; Rinny Rorimpandey (Journal of English Culture, Language, Literature and Education, 2021)
This study aims to determine whether the E-learning method can be effective in optimizing students' reading comprehension of descriptive text with WhatsApp Application. This research was conducted in class X MIA 1 SMA Negeri 1 Buko in the academic year of 2020/2021. This study used one group-pretest-postest design of research with the data analysis was the frequency distribution of scores, mean and standard deviation. The questions from the pretest and posttest used the type of multiple-choice questions with questions about the descriptive text. From this result, it was found that the mean of posttest Y = 7.8 with standard deviation Sy = 0.79 was higher than the mean score at pretest X = 5.33 with standard deviation Sx = 0.89. It means that students' reading comprehension in the descriptive text was higher after treatment at posttest than pretest. So the researcher concluded that the application of the E-learning method through WhatsApp application was effective in optimizing students' reading comprehension of descriptive text.